Impact of V2G integration on an urban feeder in Nepal: A case of Baneshwor feeder - Sah, Rupesh Kumar; Karki, Navaraj; Adhikari, Yuvraj (Journal of Advanced College of Engineering and Management, 2024)
The increasing number of electric vehicles increases strain on distribution system. Voltage, Power loss and reliability of the system deteriorates. During peak load charging of these vehicle, stability of the system will more degrade. This paper proposes V2G control scheme. A coordinated way of charging and discharging of EV. The vehicles are charging during off-peak hour when tariff rate is low and discharge during peak hour when tariff rate is high. The penetration of V2G increased system performance. The impact of Fast charging station is also considered. It is assumed that charging station operates whole day. A smart charging control is considered for V2G scheme. The charging station is placed using a novel reliability index approach called Electric Vehicle Placement Index (EVPI). Genetic Algorithm is used for optimal placement of CS. The thesis aims to decrease the peak load demand and increase the reliability of the system. The analysis is carried out in IEEE 33 bus radial system and then implemented on real-time Baneshwor feeder distribution system.